2022
DOI: 10.3390/machines10020077
|View full text |Cite
|
Sign up to set email alerts
|

Turbine Rotor Dynamics Models Considering Foundation and Stator Effects

Abstract: The paper deals with the modelling of turbine rotors, including a foundation and stator parts, and with their dynamic analysis. The dynamics of turbines can be strongly influenced by the effects of a rotor foundation, and therefore suitable modelling approaches should be developed to obtain proper analysis tools. The standard methods for the modelling of rotating shafts are summarized in the paper, and two approaches to including foundation effects into dynamic models are introduced. The approach based on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…In further research, this problem will be addressed, by supplementing the proposed method with other state-of-the-art techniques. The method of the complex dynamic matrix of compliances is well suited to calculate the foundation and support behavior of rotating systems [40].…”
Section: Discussionmentioning
confidence: 99%
“…In further research, this problem will be addressed, by supplementing the proposed method with other state-of-the-art techniques. The method of the complex dynamic matrix of compliances is well suited to calculate the foundation and support behavior of rotating systems [40].…”
Section: Discussionmentioning
confidence: 99%
“…Machines 2022, 10, x FOR PEER REVIEW 3 of 19 analysis of rotor system with uncertainty [19,20]. Therefore, this paper presents a method to study the dynamic characteristics of the multi-stage centrifugal pump rotor system, where the structural parameters of the sliding bearing are uncertain because of the manufacture errors.…”
Section: Dynamic Modeling Of the Bearing-rotor System Of A Multi-stag...mentioning
confidence: 99%
“…Although effects of the manufacturing errors on the dynamic characteristics of the sliding bearing have already been investigated, how the manufacturing errors further affect the dynamic characteristics of the sliding bearing-rotor system have not been studied. Moreover, many studies have already found that the parameter disturbances of the rotor system can affect its stability and provided theoretical methods to perform the dynamic analysis of rotor system with uncertainty [19,20]. Therefore, this paper presents a method to study the dynamic characteristics of the multi-stage centrifugal pump rotor system, where the structural parameters of the sliding bearing are uncertain because of the manufacture errors.…”
Section: Introductionmentioning
confidence: 99%
“…Throughout this work, the bars denotes that the displacements are not measured from the equilibrium position. The equation of motion of the system can be written in general form as [13,14,19],…”
Section: Rotor-foundation Modelmentioning
confidence: 99%
“…- Figures [17][18][19] show the radial displacements and orbits at several points of the rotor-foundation system for Ω = 3000 rpm and Ω = 4000 rpm: of the rotor at bearing 1 (node 6 in Fig. 1a), disk 2 (node 15 in Fig.…”
Section: Realistic Rotor-foundation Systemmentioning
confidence: 99%